2008
DOI: 10.1007/s12032-008-9104-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a cyclooxygenase-1-selective inhibitor in a mouse model of ovarian cancer, administered alone or in combination with ibuprofen, a nonselective cyclooxygenase inhibitor

Abstract: Nonsteroidal anti-inflammatory drugs (NSAIDs) are known to be potent inhibitors of the cyclooxygenases. The present study was designed to investigate the effects of a cyclooxygenase (COX)-1 inhibitor, SC-560, administered alone or in combination with ibuprofen on the growth inhibition of s.c. human ovarian SKOV-3 carcinoma and on angiogenesis. The effects of SC-560 and ibuprofen on tumor growth inhibition have been examined in mouse ovarian cancer models. Angiogenesis of both COX inhibitors was measured by rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 41 publications
1
22
0
Order By: Relevance
“…Similarly, curcumin has been reported to be two folds more potent inhibitor of COX-1 than that of COX-2 (COX-1 IC 50 ¼50 μM, COX-2 IC 50 4100 μM) [1]. Furthermore, in conformity with our in silico results, Li et al [16] has demonstrated inhibition of tumor growth by ibuprofen in a mouse cancer model by preferential inhibition of COX-1. On the other hand, aspirin has been shown to inhibit growth of many types of tumors including breast cancer by preferential inhibition of COX-2 [17].…”
Section: S No Ligandssupporting
confidence: 89%
See 1 more Smart Citation
“…Similarly, curcumin has been reported to be two folds more potent inhibitor of COX-1 than that of COX-2 (COX-1 IC 50 ¼50 μM, COX-2 IC 50 4100 μM) [1]. Furthermore, in conformity with our in silico results, Li et al [16] has demonstrated inhibition of tumor growth by ibuprofen in a mouse cancer model by preferential inhibition of COX-1. On the other hand, aspirin has been shown to inhibit growth of many types of tumors including breast cancer by preferential inhibition of COX-2 [17].…”
Section: S No Ligandssupporting
confidence: 89%
“…Many efforts have been made to find out the possible relevance of COX-1 and COX-2, in relation to various pathophysiological conditions, using specific as well as non-specific drugs and inhibitors. Thus, ibuprofen, a commonly used nonstreroidal anti-inflammatory drug (NSAID), has recently been shown to inhibit tumor growth in a mouse cancer model by preferentially inhibiting COX-1 [16]. On the other hand, aspirin (another NSAID) has been reported to inhibit growth of many types of tumors including breast cancer by preferential inhibition of COX-2 [17].…”
Section: Introductionmentioning
confidence: 99%
“…Our results have shown that SC-560 and taxol therapy inhibited VEGF mRNA expression, and a combination therapy of the two drugs demonstrated a synergistic effect. Previous studies have found that the expression of COX-1 leads to an increased expression of VEGF and that the inhibition of COX-1 reverses this response (15,34,35). The above studies indicate that COX-1 inhibitors may indirectly inhibit VEGF expression by inhibiting COX-1 expression.…”
mentioning
confidence: 59%
“…Since he was 40 years old when he flared and his BMI was low, the risk of having elevated VEGF was high [43] possibly making him a poorer candidate for the effects of a high FA dose. [46][47][48]. Theoretically depending on which type of NOS is preserve these drugs could improve or worsen psoriasis.…”
Section: Commentmentioning
confidence: 99%